A thermal battery positive electrode material based on anion substitution and a preparation method thereof
By replacing part of the anions on the surface of the positive electrode material of the thermal battery, forming an interface modification layer, improving the interface characteristics between the electrode and the electrolyte, solving the problem of poor discharge performance of the positive electrode material of the thermal battery, improving the electrical performance and capacity of the battery, and meeting the high-performance ratio Energy and miniaturization demand.
Patent Information
- Application Number
- CN202211565051.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-07
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2042-12-07
AI Technical Summary
The current hot battery positive electrode materials have poor discharge performance at low temperature and high current, mainly due to the insufficient conductivity of the electrode materials and the low electrochemical reaction rate between the electrolyte and the electrode materials, resulting in large polarization internal resistance during the discharge process, making it difficult to significantly improve existing additives. Performance cannot meet the development needs of high specific energy and miniaturization.
By forming an interface modification layer on the surface of the positive electrode material of the thermal battery, replacing some anions with different types of anions, improving the interface characteristics between the positive electrode material and the electrolyte, increasing the electron-ion exchange transfer rate, and reducing polarization impedance.
Without significantly reducing the active substance content of the positive electrode material, the electrical performance of the thermal battery is significantly improved, the discharge performance and capacity are improved, and the development needs of high specific energy and miniaturization are met.
Smart Images

Figure HDA0003986265300000011 
Figure HDA0003986265300000012
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of thermal batteries, and in particular to a thermal battery positive electrode material based on anion substitution and a preparation method thereof. Background Art
[0002] As a heat-activated storage battery, thermal batteries mainly include positive electrodes, electrolytes, negative electrodes, heating materials, etc. They have the advantages of short activation time, long storage time and wide operating temperature range, and are therefore widely used in various military and civilian fields.
[0003] At present, thermal batteries mainly use oxides such as VO2, lithiated V2O5, Cu-VO compounds, MnO2, etc., sulfides such as FeS2, CoS2, Fe-Co-S2, NiS2, etc., and halogen salts such as NiCl2, NiF2, CuF2, FeF3, etc. as positive electrode active materials. When using the above-mentioned positive electrode materials, there are problems such as poor low-temperature and large-current discharge performance. The main reasons are that the conductivity of the electrode material is not high enough, the electrochemical reaction rate between the electrolyte and the electrode material is low, etc., which leads to a large polarization during the discharge process. Usually, thermal batteries improve the interface characteristics between the positive electrode material and the electrolyte by adding additives such as C and Ag to the positive electrode active material. However, the existing additives will not only significantly reduce the content of active substances in the positive electrode material of the thermal battery, but also reduce the Li to a certain extent. + The diffusion rate in the porous electrode does not significantly improve the discharge performance of the thermal battery positive electrode active material, making it difficult to meet the development needs of high specific energy and miniaturization of thermal batteries. In view of this, it is very meaningful to provide a thermal battery positive electrode material with high performance and a preparation method thereof. Summary of the invention
[0004] In order to solve the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a thermal battery positive electrode material based on anion substitution and a preparation method thereof, which can effectively improve the interface characteristics between the thermal battery positive electrode material and the electrolyte without significantly reducing the content of active substances in the positive electrode material, accelerate the ion-electron exchange transfer process at the interface, thereby effectively solving the problems of large polarization internal resistance in the discharge process of the existing thermal battery positive electrode material.
[0005] The technical solution of the present invention to solve the above technical problems is as follows: a thermal battery positive electrode material based on anion substitution is provided, comprising: a positive electrode material matrix and an interface modification layer attached to the surface of the positive electrode material matrix; the interface modification layer is prepared by replacing part of the anions in the surface layer of the positive electrode material with different types of anions.
[0006] The beneficial effects of the present invention are as follows: the above-mentioned positive electrode material matrix is a conventional thermal battery positive electrode material, and the present invention modifies the surface of the conventional thermal battery positive electrode material to form a positive electrode material matrix and an interface modification layer attached to the surface of the positive electrode material matrix. That is to say, a part of the anions in the surface layer of the positive electrode material is replaced by anions of different types, that is, the replaced anions in the modification layer are different from the anions before being replaced, so that an interface modification layer is formed, and the part within the surface layer of the positive electrode material is not replaced, and this part is called the positive electrode material matrix. After the present invention modifies the surface of the thermal battery positive electrode material, defects can be introduced to change the electronic structure of the surface layer of the positive electrode material, improve the interface characteristics between the positive electrode material and the electrolyte, accelerate the interface electron-ion exchange transfer, thereby reducing the polarization impedance, and after the positive electrode material is applied to thermal battery products, the electrical performance of the battery can be improved.
[0007] On the basis of the above technical solution, the present invention can also be improved as follows:
[0008] Furthermore, the thickness of the surface layer of the positive electrode material is 0.1-5 nm.
[0009] Furthermore, the molar percentage of the replacing anions in the surface layer of the positive electrode material is 10-80% of the anions in the surface layer.
[0010] The beneficial effect of adopting the above-mentioned further technical scheme is as follows: the positive electrode material has a certain thickness (20nm-100um), and only part of the anions in the surface layer of the positive electrode material are replaced by other different types of anions, while the active components within the surface layer of the positive electrode material are unchanged. The thickness of the surface layer of the positive electrode material is 0.1-5nm, and the molar percentage of the replaced anions in the surface layer anions in this thickness is 10-80% (for example, part of the S in the surface layer is replaced by N, then the molar percentage of N in the surface layer anions is 10-80%), which has little effect on the content of active substances in the positive electrode material. Without significantly reducing the content of active substances in the positive electrode material, it can effectively improve the interface characteristics between the positive electrode material of the thermal battery and the electrolyte, accelerate the ion-electron exchange transfer process at the interface, thereby effectively solving the problems of large polarization internal resistance in the discharge process of the existing positive electrode material of the thermal battery. When the molar ratio of the substituted anions is too much or too little, that is, it exceeds the range required by the present invention, it will affect the electrical performance of the battery. Only by improving the interface characteristics between the thermal battery positive electrode material and the electrolyte within the above-mentioned molar ratio range and accelerating the ion-electron exchange transfer process at the interface can the problems of large polarization internal resistance during discharge of existing thermal battery positive electrode materials be effectively solved.
[0011] Furthermore, the anions on the surface of the positive electrode material are replaced by at least one of the following anions: - , Cl - , O 2- and N 3- .
[0012] Further, the positive electrode material matrix is at least one of FeS2, CoS2, Fe-Co-S2, NiS2, Fe-Ni-S2, Ni-Co-S2, SnS2, Sn-Ti-S2, Sn-Zr-S2, NiCl2, NiF2, Ni-(F-Cl)2, CuF2, CuCl2, Cu-(F-Cl)2, FeF3, FeCl3, Fe-(F-Cl)3, CrF3, CrCl3, Cr(F-Cl)3, VO2, Li-VO, CuO, Cu2O, Cu-VO, MnO2, Li-Mn-O, AgCrO4, CrO2 and CaCrO4.
[0013] The above-mentioned method for preparing the positive electrode material of the thermal battery based on anion substitution comprises the following steps:
[0014] The positive electrode material is placed in gas or liquid for heat treatment, so that the anions in the surface layer of the positive electrode material are replaced by the anions in the gas or liquid, forming an interface modification layer attached to the positive electrode material matrix, and obtaining the anion-substituted thermal battery positive electrode material.
[0015] The beneficial effects of the present invention are as follows: the gas or liquid contains replacement anions, the anions are in contact with the positive electrode material in the form of gas or liquid, and then heat treated. During the heat treatment, through the atomic replacement reaction, some anions in the surface layer of the positive electrode material are replaced by different types of anions to form an interface modification layer, which is attached to the positive electrode material matrix, thus forming an anion-substituted thermal battery positive electrode material.
[0016] Furthermore, the gas includes at least one of NH3, HF, F2, O2, HCl and Cl2.
[0017] The above-mentioned gas can be obtained by solid decomposition, liquid decomposition, etc., for example, it can be obtained by decomposing solid ammonium nitrate, ammonium fluoride, ammonium chloride and other substances, or by decomposing it from ammonia water, or by precipitating it from its corresponding aqueous solution or alcohol solution.
[0018] Furthermore, the above liquid includes F - , Cl - , O 2- , or N 3- of solution or molten salt.
[0019] Furthermore, the solvent in the solution is water or ethanol.
[0020] Furthermore, the cation in the solution or molten salt is Li + 、Na + , K + , Cu 2+ 、V4+ 、V 5+ Sn 2+ , Fe 2+ , Fe 3+ Cr 3+ , Mn 2+ , Mn 3+ , Mn 4+ 、Ag + and Ca 2+ At least one of .
[0021] Furthermore, the heat treatment temperature is 120-800°C, and the insulation time is 0.05-48h; preferably, the heat treatment temperature is 180-700°C, and the insulation time is 15min-24h.
[0022] After the heat treatment is completed, the above-mentioned processes may also include filtering, washing, drying and the like.
[0023] The present invention has the following beneficial effects:
[0024] The present invention heat-treats the positive electrode material of a thermal battery in an atmosphere or solution containing anionic components, so that part of the anions in the surface layer of the positive electrode material are replaced by anions of another type, thereby changing the electronic structure of the surface layer of the positive electrode material by introducing defects, improving the interface characteristics between the positive electrode material and the electrolyte, accelerating the surface interface electron-ion exchange transfer process, thereby reducing polarization impedance, and greatly improving the performance of the battery when the high-performance positive electrode material is applied to thermal battery products. The invention has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a microscopic morphology of the thermal battery positive electrode material based on anion substitution prepared in Example 1 of the present invention.
[0026] Figure 2 This is a discharge performance diagram of the thermal battery positive electrode material based on anion substitution prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0027] The following examples are only used to explain the present invention and are not intended to limit the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0028] Embodiment 1:
[0029] A thermal battery positive electrode material based on anion substitution is obtained by surface modification of a conventional thermal battery positive electrode material. The conventional thermal battery positive electrode material used in this embodiment is CoS2, and its particle size is 500nm. The finally obtained thermal battery positive electrode material based on anion substitution includes: a positive electrode material matrix and an interface modification layer attached to the surface of the positive electrode material matrix; the interface modification layer is obtained by replacing part of the anions in the surface layer of the positive electrode material with different types of anions.
[0030] The matrix of the positive electrode material is CoS2, the thickness of the surface layer of the positive electrode material is 2 nm, part of the S in the surface layer is replaced by N to form an interface modification layer, and the molar percentage of N in the surface layer is 61%.
[0031] The above-mentioned method for preparing the positive electrode material of the thermal battery based on anion substitution comprises the following steps:
[0032] The positive electrode material CoS2 was transferred to an atmosphere furnace, and after NH3 was introduced, the temperature was raised to 400°C and kept warm for 15 minutes so that the thickness of the N-containing surface layer reached 2nm. It was then cooled to room temperature to obtain a thermal battery positive electrode material based on anion substitution.
[0033] During the above-mentioned process of introducing NH3, the gas flow rate of NH3 was controlled at 100 ml / min.
[0034] Embodiment 2:
[0035] A thermal battery positive electrode material based on anion substitution is obtained by surface modification of a conventional thermal battery positive electrode material. The conventional thermal battery positive electrode material used in this embodiment is Fe 0.5 Co 0.5 S2, with a particle size of 2um, the final thermal battery positive electrode material based on anion substitution includes: a positive electrode material matrix and an interface modification layer attached to the surface of the positive electrode material matrix; the interface modification layer is prepared by replacing part of the anions in the surface layer of the positive electrode material with different types of anions.
[0036] The above cathode material matrix is Fe 0.5 Co 0.5 S2, the thickness of the surface layer of the positive electrode material is 1.5 nm, and part of the S in the surface layer is replaced by F to form an interface modification layer, and the molar percentage of F in the surface layer is 70%.
[0037] The above-mentioned method for preparing the positive electrode material of the thermal battery based on anion substitution comprises the following steps:
[0038] 10g Fe 0.5 Co 0.5S2 and 100g LiF-KF-FeF2 molten salt are mixed to obtain a mixture, the mixture is placed in a graphite crucible, and then transferred to an inert atmosphere furnace and heated to 520°C and kept warm for 2h. After the insulation, the product is cooled to room temperature and impurities such as excess molten salt are washed away with deionized water. After drying, a thermal battery positive electrode material based on anion substitution is obtained.
[0039] Embodiment 3:
[0040] A thermal battery positive electrode material based on anion substitution is obtained by surface modification of a conventional thermal battery positive electrode material. The conventional thermal battery positive electrode material used in this embodiment is CuF2, and its particle size is 500nm. The finally obtained thermal battery positive electrode material based on anion substitution includes: a positive electrode material matrix and an interface modification layer attached to the surface of the positive electrode material matrix; the interface modification layer is obtained by replacing part of the anions in the surface layer of the positive electrode material with different types of anions.
[0041] The matrix of the positive electrode material is CuF2, the thickness of the surface layer of the positive electrode material is 1.0 nm, part of F in the surface layer is replaced by O to form an interface modification layer, and the molar percentage of O in the surface layer is 30%.
[0042] The above-mentioned method for preparing the positive electrode material of the thermal battery based on anion substitution comprises the following steps:
[0043] 10g CuF2 and 50g Li2O-LiF molten salt (LiF in the molten salt also plays a role in lowering the melting point) are mixed to obtain a mixture, which is placed in a graphite crucible and then transferred to an inert atmosphere furnace and heated to 700°C for 2 hours. After the insulation, the product is cooled to room temperature and impurities such as excess molten salt are washed off with deionized water. After drying, a thermal battery positive electrode material based on anion substitution is obtained.
[0044] Embodiment 4:
[0045] A thermal battery positive electrode material based on anion substitution is obtained by surface modification of a conventional thermal battery positive electrode material. The conventional thermal battery positive electrode material used in this embodiment is CuO, and its particle size is 20um. The finally obtained thermal battery positive electrode material based on anion substitution includes: a positive electrode material matrix and an interface modification layer attached to the surface of the positive electrode material matrix; the interface modification layer is obtained by replacing part of the anions in the surface layer of the positive electrode material with different types of anions.
[0046] The matrix of the positive electrode material is CuO, the thickness of the surface layer of the positive electrode material is 0.5 nm, part of O in the surface layer is replaced by F to form an interface modification layer, and the molar percentage of F in the surface layer is 80%.
[0047] The above-mentioned method for preparing the positive electrode material of the thermal battery based on anion substitution comprises the following steps:
[0048] 20 g of CuO was mixed with 80 mL of HF (0.01 mol / L) aqueous solution, and the mixture was transferred to a reactor, then heated to 180°C, kept warm for 24 hours, and finally cooled to room temperature. After filtering, washing, and drying, a thermal battery positive electrode material based on anion substitution was obtained.
[0049] Embodiment 5:
[0050] A thermal battery positive electrode material based on anion substitution is obtained by surface modification of a conventional thermal battery positive electrode material. The conventional thermal battery positive electrode material used in this embodiment is NiCl2, and its particle size is 10um. The finally obtained thermal battery positive electrode material based on anion substitution includes: a positive electrode material matrix and an interface modification layer attached to the surface of the positive electrode material matrix; the interface modification layer is obtained by replacing part of the anions in the surface layer of the positive electrode material with different types of anions.
[0051] The matrix of the positive electrode material is NiCl2, the thickness of the surface layer of the positive electrode material is 3 nm, the Cl in the surface layer is replaced by F to form an interface modification layer, and the molar percentage of F in the surface layer is 50%.
[0052] The above-mentioned method for preparing the positive electrode material of the thermal battery based on anion substitution comprises the following steps:
[0053] 10g NiCl2 and 10g LiCl-LiF molten salt are mixed to obtain a mixture, which is placed in a graphite crucible and then transferred to an inert atmosphere furnace and heated to 550°C for 2 hours. After the insulation, the product is cooled to room temperature and impurities such as excess molten salt are washed away with deionized water. After drying, a thermal battery positive electrode material based on anion substitution is obtained.
[0054] Embodiment 6:
[0055] A thermal battery positive electrode material based on anion substitution is obtained by surface modification of a conventional thermal battery positive electrode material. The conventional thermal battery positive electrode material used in this embodiment is CoS2, and its particle size is 500nm. The finally obtained thermal battery positive electrode material based on anion substitution includes: a positive electrode material matrix and an interface modification layer attached to the surface of the positive electrode material matrix; the interface modification layer is obtained by replacing part of the anions in the surface layer of the positive electrode material with different types of anions.
[0056] The matrix of the positive electrode material is CoS2, the thickness of the surface layer of the positive electrode material is 3 nm, part of the S in the surface layer is replaced by N to form an interface modification layer, and the molar percentage of N in the surface layer is 71%.
[0057] The above-mentioned method for preparing the positive electrode material of the thermal battery based on anion substitution comprises the following steps:
[0058] The positive electrode material CoS2 was transferred to an atmosphere furnace, and after NH3 was introduced, the temperature was raised to 400°C and kept warm for 30 minutes so that the thickness of the N-containing surface layer reached 3nm. It was then cooled to room temperature to obtain a thermal battery positive electrode material based on anion substitution.
[0059] During the above-mentioned process of introducing NH3, the gas flow rate of NH3 was controlled at 100 ml / min.
[0060] Embodiment 7:
[0061] A thermal battery positive electrode material based on anion substitution is obtained by surface modification of a conventional thermal battery positive electrode material. The conventional thermal battery positive electrode material used in this embodiment is CoS2, and its particle size is 500nm. The finally obtained thermal battery positive electrode material based on anion substitution includes: a positive electrode material matrix and an interface modification layer attached to the surface of the positive electrode material matrix; the interface modification layer is obtained by replacing part of the anions in the surface layer of the positive electrode material with different types of anions.
[0062] The matrix of the positive electrode material is CoS2, the thickness of the surface layer of the positive electrode material is 0.8 nm, part of the S in the surface layer is replaced by N to form an interface modification layer, and the molar percentage of N in the surface layer is 38%.
[0063] The above-mentioned method for preparing the positive electrode material of the thermal battery based on anion substitution comprises the following steps:
[0064] The positive electrode material CoS2 was transferred to an atmosphere furnace, and after NH3 was introduced, the temperature was raised to 400°C and kept warm for 6 minutes so that the thickness of the N-containing surface layer reached 0.8nm. It was then cooled to room temperature to obtain a thermal battery positive electrode material based on anion substitution.
[0065] During the above-mentioned process of introducing NH3, the gas flow rate of NH3 was controlled at 100 ml / min.
[0066] Test Example 1
[0067] The thermal battery positive electrode material based on anion substitution obtained in the above embodiment is tested, and it can be found that some anions in the surface layer of the positive electrode material are replaced by other anions added. The modified thermal battery positive electrode material is used for discharge performance testing, which can significantly improve the discharge performance of the positive electrode material. Specifically, taking Example 1 as an example, the anion-substituted thermal battery positive electrode material obtained in Example 1 has a microscopic morphology as shown in FIG. Figure 1 As shown. Figure 1It can be seen that the lattice of the surface layer of the positive electrode material replaced by anions is distorted compared with its inner layer, indicating that part of the S in the surface layer of the CoS2 positive electrode material is replaced by N.
[0068] The discharge performance of the thermal battery positive electrode material based on anion substitution prepared in Example 1 was compared before and after anion substitution, with a discharge temperature of 525°C and a discharge current density of 300 mA cm -2 The comparison results are shown in Figure 2 .Depend on Figure 2 It can be seen that when some anions in the surface layer of the positive electrode material are replaced by other different types of anions, its discharge capacity can be increased from 280 mAh g -1 Increased to 390mAh g -1 , indicating that some anions in the surface layer are replaced, which can effectively improve its discharge performance. In addition, the final discharge capacity is different with different amounts of replaced anions. Within a certain range, the higher the amount of replaced anions, the greater the improvement in discharge capacity.
[0069] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a thermal battery positive electrode material based on anion substitution, characterized in that: The positive electrode material is placed in a gas or liquid for heat treatment, so that the anions in the surface layer of the positive electrode material are replaced by different types of anions in the gas or liquid, forming an interface modification layer attached to the positive electrode material matrix, and obtaining an anion-substituted thermal battery positive electrode material; The gas comprises at least one of HF, F2, HCl and Cl2; The liquid includes Cl - , O 2- or N 3- of solution or molten salt.
2. The preparation method according to claim 1, characterized in that: The solvent in the solution is water or ethanol; the cation in the solution or molten salt is Li + 、Na + , K + , Cu 2+ 、V 4+ 、V 5+ Sn 2+ , Fe 2+ , Fe 3+ Cr 3+ , Mn 2+ , Mn 3+ , Mn 4+ 、Ag + and Ca 2+ At least one of .
3. The preparation method according to claim 1, characterized in that: The heat treatment temperature is 120-800°C, and the holding time is 0.05-48h.
4. A thermal battery positive electrode material based on anion substitution prepared by the preparation method according to any one of claims 1 to 3.
5. The thermal battery positive electrode material based on anion substitution according to claim 4, characterized in that: include: A cathode material matrix and an interface modification layer attached to the surface of the cathode material matrix; The interface modification layer is prepared by replacing part of the anions in the surface layer of the positive electrode material with different types of anions.
6. The thermal battery positive electrode material based on anion substitution according to claim 5, characterized in that: The thickness of the surface layer of the positive electrode material is 0.1-5nm.
7. The thermal battery positive electrode material based on anion substitution according to claim 5 or 6, characterized in that: The molar percentage of the replacement anions in the surface layer of the positive electrode material is 10-80% of the anions in the surface layer.
8. The thermal battery positive electrode material based on anion substitution according to claim 7, characterized in that: The anions on the surface of the positive electrode material are replaced by at least one of the following anions: F - , Cl - , O 2- and N 3- .
9. A thermal battery, characterized in that: The invention comprises the thermal battery positive electrode material based on anion substitution as described in any one of claims 4 to 8.
